The Influence Of Corporate Governance, Profitability, Leverage , And Technological Innovation Mechanisms On Sustainability Reporting - Umi Masruroh; Dirvi Surya Abbas; Imam Hidayat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to test and analyze the influence of Corporate Governance, Profitability, Leverage, and Technological Innovation Mechanisms on Sustainability Reporting in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach. The sample of this study is 17 manufacturing companies listed on the Indonesia Stock Exchange for the 2019 – 2023 period. Sample determination using purposive sampling. Testing using Eviews media 12. Data collection uses secondary data. The results of the study show that the variables of the corporate governance mechanism proxied with CGPI, profitability, and technological innovation have a positive effect on sustainability reporting. Meanwhile, leverage in this study has a negative effect on sustainability reporting.